Landscape in the R. L. Stevenson's Adventurous Prose - Hrubešová, Magdaléna (Univerzita Pardubice, 2021)
The primary focus of this work is the portrayal of a landscape and its functions in the work of Robert Louis Stevenson. The works discussed are Treasure Island and Kidnapped. The first part of this paper is concerned with the description of influences which led to the boom of adventure literature in the nineteenth century. In addition, a brief discussion of the Romanticism is included. The second part of this thesis concerns analysing the usage and portrayal of the landscape in both novels. All findings are summarised in the final chapter.
Krajina v dobrodružné próze R.L. Stevensona
Keywords: landscape; Stevenson, Robert Louis; Romanticism; island; sea; Burke, Edmund; krajina; Stevenson, Robert Louis; romantismus; ostrov; moře; Burke, Edmund